THE LINKAGE BETWEEN CHANGE COMMUNICATION AND BEHAVIORAL RESISTANCE TO CHANGE: MODERATING EFFECT OF TRUST IN MANAGEMENT - Zulkifli Nurul Haqq (Universitas Muhammadiyah Kendari, 2021)
This study aims to investigate the impact of change communication and trust in management on behavioral resistance to change by using social exchange theory. Also, this study sought to examine the moderating effect of trust in management in the relationship between change communication and behavioral resistance to change. This research involved Shariah Rural Bank in which the middle change implementation. The designed questionnaires were distributed to all employees (n = 96) and returned all. In addition, PLS-SEM is used as a method of research analysis. The results show that change communication becomes a significant predictor towards behavioral resistance to change. Unfortunately, trust in management has not a direct significant relationship with behavioral resistance to change. However, this study found the significant moderating effect of trust in management in the relationship between change communication and behavioral resistance to change. Finally, this study offers several implications, both theoretically and practically.